Employing Augmented Reality in Reading Classes for Indonesian EFL Junior High School Students: A Perspective Analysis - Nyudak, Isidorus Bagus Geovenda; Pratama, Dewa Gede Saka; Sugiani, Ni Nyoman; Putra, Nyoman Adi Jaya (Jurnal Pedagogy, 2024)
In an educational context, reading skills are essential for students, particularly in the ELT context. Good reading skills are not only profitable for fostering vocabulary. They are also essential for fostering students’ understanding of complex text. Integrating technology, especially Augmented Reality (AR), becomes one of the transformative keys to gaining students’ engagement and enthusiasm for learning activities. With an explanatory sequential mixed method and a convenient sampling technique, this comprehensive study observes eighth-grade students’ perspectives on AR implementation in their reading class. Of 135 students, 51 were conveniently involved in the study in the first phase. Besides, 5 of 51 students were invited to interview sessions in the second phase. The essential findings of this study revealed that the use of AR eased students’ understanding of the text, especially texts using present continuous tense. The use of AR enhanced students’ engagement and involvement in instructional activities. The use of AR provided a practical and interactive learning climate. By this point, AR implementation in this study fulfilled students’ needs and fostered an adaptive and responsive learning environment. AR provides a dynamic and exciting learning environment that boosts students’ reading skills. The AR utilization allows students to interact directly with the reading content and strengthen their understanding of the scenario. That reveals the enormous potential of AR technology in transforming how we conduct instructional activities, particularly in enhancing reading skills and comprehension for eighth-grade students.